Allogeneic transplantation in multiple myeloma: long-term follow-up and cytogenetic subgroup analysis - Knop, Stefan; Engelhardt, Monika; Liebisch, Peter; Meisner, Christoph; Holler, Ernst; Metzner, Bernd; Peest, Dietrich; Kaufmann, Martin; Bunjes, Donald; Straka, Christian; Fischer, Thomas; Sezer, Orhan; et al. (Leukemia, 2019)
This phase 3 trial compared tandem autologous stem cell transplantation (autoSCT) versus autoSCT followed by reduced-intensity conditioning allogeneic stem cell transplantation (auto/alloSCT) in patients with newly diagnosed multiple myeloma (MM) with deletion of (del) chromosome 13q (del13q). The availability/absence of a human leukocyte antigen-matched-related or matched-unrelated donor (MUD) determined the nature of the second SCT. The primary endpoint was progression-free survival (PFS) in the intention-to-treat population (n = 199). Auto/alloSCT was performed in 126 patients; 74 received MUD allografts. After 91 months median follow-up, median PFS with auto/allo versus tandem autoSCT was 34.5 versus 21.8 months (P = 0.003; adjusted hazard ratio 0.55, 95% confidence interval 0.36–0.84). Median overall survival (OS) was 70.2 versus 71.8 months (P = 0.856). Two-year non-relapse mortality with auto/allo versus tandem autoSCT was 14.3% versus 4.1% (P = 0.008). In patients harboring both del13q and del17p, median PFS and OS were 37.5 and 61.5 months with auto/allo (n = 19) versus 6.1 and 23.4 months with tandem autoSCT (n = 6) (P = 0.0002 and 0.032). Our findings suggest that auto/alloSCT significantly extends PFS versus tandem autoSCT in del13q MM, and indicate some survival benefit for first-line alloSCT in high-risk MM.
CRIS-Team Scopus Importer:2019-09-17